Crenças parentais e iniciação do consumo de álcool entre adolescentes brasileiros - Sousa, Gyzelda de Barros (2023)
Adolescence, the transition phase between childhood and adulthood, can be permeated by behaviors that can lead to greater vulnerability to the consumption of alcohol and other drugs. The use of alcohol can contribute to family problems, such as the breaking of affective bonds, aggressiveness and social vulnerability. In addition, parental beliefs and practices such as alcohol consumption in the presence of children can influence early use by adolescents. In this sense, educational programs focused on preventing the use of alcohol are recommended internationally, highlighting those focused on the family, such as the governmental program Famílias Fortes (PFF). The study aimed to verify the association between initiation of alcohol consumption (binge drinking) and parental beliefs among families and adolescents aged 11 to 14 years, participants of a government program. This is a cross sectional study, nested within a cluster-randomized controlled trial. The study examined baseline trial data collected prior to intervention delivery. The sample consisted of 859 families that use the Social Assistance Reference Centers (CRAS) and other social centers indicated by 12 municipalities agreed by the Ministry of Women, Family and Human Rights (MMFDH). Keywords: Adolescent health; Consumption of Alcoholic Beverages; Parenting; Oral Substance Abuse; Prevention. As a result, in relation to the age of adolescents from 12 to 14 years old, there is a percentage of 48.2% among boys and 51.1% among girls. Among adults, most were female (91%) with a mean age of 39.5 years (SD= .15). As for the use of drugs in life, 12.3% of the adolescents reported that they had already consumed alcohol and 3.6% carried out the practice of binge drinking. In multivariate logistic regression, it was observed that parents who think it is safer to teach their children to drink at home increase the chances of their children starting to use alcohol by 97%. Our study identified that some parental beliefs, such as 'teaching your child to drink at home' and thinking that 'adolescent drinking at parties is not a problem', are associated with early initiation of alcohol use and the practice of binge drinking by adolescents . It is concluded that it is important to develop programs for families that clarify the consequences of the early use of alcoholic beverages by adolescents with a focus on identifying parental beliefs and how they can influence decisions regarding the consumption of alcohol and other drugs. However, in the present study, the parents' beliefs about their children's alcohol consumption proved to be one of the favorable factors for starting consumption. In this sense, the nurse's role is essential in understanding existing conflicts and deepening the genesis of parental relationships, working with the health team to demystify beliefs about alcohol, thus forming bonds with a focus on health promotion.